Relations between digestibility and structures of pumpkin starches and pectins. (September 2020) - Bai, Yeming; Zhang, Mengshan; Chandra Atluri, Sharat; Chen, Jialin; Gilbert, Robert G.
Abstract: Pumpkin has human nutritional benefits, arising from its high content of starch and of dietary fibres such as pectins. Pectin has been found to slow starch digestion in digesta, which is related to the reduction of propensity towards diet-related diseases such as diabetes, but whether un-extracted pectin could influence in vitro digestibility of in situ starch in vegetable is unknown. In this paper, the molecular structures of pectin and starch from 13 commercial pumpkin varieties were characterized (using HPLC and size-exclusion chromatography), and the in vitro digestion kinetics of the boiled flour measured. The structural and kinetic data were fitted to models, and correlation analysis applied to the resulting parameters to find the factors influencing the digestibility. It was found that (1) a particular structural feature of pumpkin starch was the high proportion of long amylopectin chains, (2) pumpkin pectins exhibited wide diversity in molecular structure, (3) the in vitro digestibility of pumpkin flour parameters correlated with structural parameters of both pectin (degree of esterification) and starch (average hydrodynamic radius). These results showed that both macromolecules affect pumpkin flour digestibility, and the presence of pectin as a key component of cell wall materials contribute to the provision of a barrier between amylase and starch. Unlike the digestion of pure starch, where the starch structure is the major determinant in digestibility, the digestion of pumpkin flour depends also on the complex network of pumpkin polysaccharides. Graphical abstract: Image 1 Highlights: Pumpkin starch contains a high proportion of long amylopectin chains. Pumpkin pectin exhibits a diversity in molecular structures. The pumpkin flour in vitro digestibility showed great differences among varieties. Both starch and pectin correlated to in vitro digestibility of pumpkin flour.